2020
DOI: 10.37190/ppmp/127883
|View full text |Cite
|
Sign up to set email alerts
|

Improved flotation of auriferous arsenopyrite by using a novel mixed collector in weakly alkaline pulp

Abstract: The purpose of using a mixed collector is to increase both flotation efficiency and selectivity. The mixed collector of potassium isopentyldithiocarbonate and N-dodecyl mercaptan exhibits high efficiency for the flotation of auriferous arsenopyrite, and the 2:1 mixing mass ratio of potassium isopentyldithiocarbonate and N-dodecyl mercaptan is preferred. Batch flotation tests indicate that a concentrate with the grade of 47.58 g/Mg Au and the recovery of 86.45% Au is achieved by using the mixed potassium isopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…6(c), for the flotation concentrate of the mixed arsenopyrite/muscovite minerals without SP, the arsenopyrite particles were coated with numerous muscovite fines, and the muscovite fines and arsenopyrite fines were agglomerated. In the mixed flotation process, the slime coating or coagulation between muscovite and arsenopyrite which prevents the flotation of arsenopyrite particles, and results in the inclusion of muscovite into the concentrate (Wang et al, 2020). As shown in Fig.…”
Section: Sem and Eds Resultsmentioning
confidence: 99%
“…6(c), for the flotation concentrate of the mixed arsenopyrite/muscovite minerals without SP, the arsenopyrite particles were coated with numerous muscovite fines, and the muscovite fines and arsenopyrite fines were agglomerated. In the mixed flotation process, the slime coating or coagulation between muscovite and arsenopyrite which prevents the flotation of arsenopyrite particles, and results in the inclusion of muscovite into the concentrate (Wang et al, 2020). As shown in Fig.…”
Section: Sem and Eds Resultsmentioning
confidence: 99%
“…The energies were negative for all four collector states, indicating that YAO adsorption on the mineral surface is possible in all its states. They concluded that a good spodumene recovery could be achieved while remaining selective due to the preferential adsorption of the collector in its four states on spodumene over the rest of the minerals [ 21 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…Different authors mixed anionic collectors with cationic collectors to evaluate their selective capacity. They also investigated the adsorption mechanisms of these collectors with zeta potential measurements, analysis of Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS), finding good separation results; however, these require further studies before being taken to an industrial level [ 21 , 22 , 23 , 24 , 25 ]. By contrast, other authors have synthesized new collectors, obtaining good flotation results, but it remains unclear what the adsorption mechanism is on the surface of the mineral [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu, Wang (8) reported that oleic acid is a widely used anionic collector in the flotation of spodumene. The maximum flotation recovery and adsorption amount of collector was obtained under slightly alkaline pH conditions.…”
Section: Enrichment Ratiomentioning
confidence: 99%